Bone Loss and Seasonal Variation in Serial DXA Densitometry – A Population-Based Study - Sirola, Joonas; Rikkonen, Toni; Honkanen, Risto; Jurvelin, Jukka S.; Tuppurainen, Marjo; Kröger, Heikki (IntechOpen, 2012)
None